Rafael BQueer: the “neon color” as a place of passage, the power that hacks chaos (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2023)
A multiartist who represents the diversity of the lgbtqiap+ cultural scene, Rafael BQueer, born in Belém, Pará, is an important name for contemporary Brazilian thinking on Drag art and a form of performance that uses provocative and destabilizers costumes. Having participated in exhibitions in institutional spaces such as MASP and MAR and held artistic residencies in New York and Salvador, BQueer transits, with great plasticity, between the visual arts, cinema, photography, carnival and other artistic languages, raising debates that revolve around concepts such as gender, sexuality, intersectionality, decoloniality, afrofuturism. In an interview for the magazine A Luz em Cena, BQueer reflects on his artistic trajectory, his dissident and disruptive political body, his experience as a “bicha preta amazônida”, in the context of today, emphasizing, for such, the construction of garments that express the “non-uniformization” of thoughts and bodily practices.
Keywords: interview; Rafael BQuee; performance; drag art; garments; LGBTQIAP; LGBT